EFFECT OF WATER STRESS ON RHIZOBIA SYMBIOSIS IN ALFALFA (MEDICAGO SATIVA L.) - A., Mouffok1*,.; M., . Belhamra2 (university of eloued جامعة الوادي, 2020)
The objective of this work was to highlight the responses to the low, moderate and severe water deficit of five varieties of alfalfa. The mechanisms studied focused on the relative water content, dry matter yield and symbiotic nitrogen fixation. The results obtained showed that the effects of water stress are manifested by a decrease in the relative water content and negatively affect vegetative growth as well as the symbiotic nitrogen fixation. The varieties studied behave differently depending on the severity of stress. However, the Diamant and Baldia varieties proved the most tolerant to the different degrees of water deficit. On the other hand, the varieties Dista and Moapa showed a significant sensitivity to the lack of water. This study could be used to define relevant criteria for drought resistance that can be used in varietal selection.
artical
Keywords: nitrogen fixation; alfalfa; tolerance; selection; water deficit.